Legal and Ethical Considerations in the Development of New Dental Materials - Hamad Yahya Al Shareef; Dr Yousef Masoud Al Haider; Ali Khalid Alsharif; Dr.Mohammed Abdullah Alobathani; Easa Saleh Ali al Mottah; Abdullah Abdulrahman Alshareef (International Journal of Medical Toxicology and Legal Medicine, 2024)
The development of new dental materials is crucial for advancing oral healthcare, offering improved durability, aesthetics, and biocompatibility. However, the innovation and commercialization of these materials raise significant legal and ethical concerns that must be carefully addressed to ensure patient safety and compliance with regulatory standards. The history of safety regulations for dental materials is deeply intertwined with the evolution of dental science, public health concerns, and advancements in materials technology. Over the centuries, as new materials were introduced into dental practice, it became evident that their safety and efficacy needed to be ensured through systematic regulation. From the early days of trial and error to the establishment of modern regulatory frameworks, the development of safety regulations for dental materials reflects growing scientific understanding and societal concerns about health and safety. The balance between innovation and patient safety remains a central concern, raising questions about how to manage potential risks while advancing dental technology. The aim of this review is to critically examine the legal and ethical considerations surrounding the development and implementation of new dental materials. It seeks to explore the regulatory frameworks governing dental material innovation, including approval processes, intellectual property rights, and liability issues. It aims also to explore the legal and ethical considerations surrounding the development and use of dental nanomaterials, with a focus on issues such as genotoxicity, carcinogenicity, cytotoxicity, biocompatibility, and biosafety. By examining these factors, we aim to provide a comprehensive framework for understanding the responsibilities of dental professionals, manufacturers, and regulators in ensuring the safe and ethical development of new dental materials. Additionally, the review aims to assess the ethical challenges through the lens of bioethics, focusing on principles such as patient safety, informed consent, and the balance between innovation and risk. The discussion concludes by emphasizing the role of dental practitioners, manufacturers, and regulatory bodies in maintaining a patient-centered approach to innovation, ensuring that legal and bioethical principles guide the future of dental material development.